Teach Yourself VISUALLY laptops - Muir, Nancy 1954- (Wiley ;, 2008)
A guide to laptop computers covers such topics as comparing laptop models, using the keyboard and touchpad, connecting to a wireless network, adding PC cards, Internet connections, and setting up a low-battery alarm.
Print version record
Keywords: Laptop computers; COMPUTERS; Hardware; Personal Computers; General; COMPUTERS; Hardware; Handheld Devices; COMPUTERS; Microprocessors; Portable computers